Could decorin be a biomarker of coronary artery disease? A pilot study in human beings - Nazemi, Saeed; Rezapour, Atefeh; Moallem, Seyed Mohammad Hassan; Afshar, Mohammad; Elyasi, Sepideh; Mashreghi Moghadam, Hamid Reza; Dargahi Zaboli, Mahmoud; Mohammadpour, Amir Hooshang (Acta Biomedica Atenei Parmensis, 2018)
Background and aim: Nowadays there is a strong necessity in identifying patients who may be exposed to the risk for future cardiovascular events like progressive atherosclerotic disease. Biomarkers are valuable tools for this purpose. Coronary artery calcification (CAC) is utilized as an important tool for the global risk assessment of cardiovascular events in individuals with intermediate risk. Decorin (DCN) is a small leucine-rich proteoglycan that induces calcification of arterial smooth muscle cell and localizes to mineral deposition in human atherosclerotic plaque. The main purpose of this clinical study was to find out the correlation between Decorin serum concentration and CAC in human for the first time. Methods: In this study 84 patients with coronary artery disease who fulfilled inclusion and exclusion criteria, entered the study. For all patients a questionnaire consisting demographic data and traditional cardiovascular risk factors were completed. CT-Angiography was carried out to determine coronary artery calcium score and ELISA method was used for measuring DCN serum concentrations. Results: No significant correlation between DCN serum concentration and total CAC score and also CAC of left anterior descending, right coronary artery, left main coronary artery and circumflex was found in the study population (P>0.05). Conclusions: On the basis of our results DCN serum concentration is not a suitable biomarker of coronary artery disease. However, more studies with higher sample size are necessary for its confirmation.